2017
DOI: 10.1016/j.actamat.2017.02.048
|View full text |Cite
|
Sign up to set email alerts
|

Formation of intermetallic δ phase in Al-10Si-0.3Fe alloy investigated by in-situ 4D X-ray synchrotron tomography

Abstract: During solidification of Fe-containing Al-Si casting alloys, various different intermetallic phases are formed. As this can have an impact on mechanical properties we investigated phase formation by applying in-situ time resolved synchrotron X-ray tomography. For a commercially pure Al-10Si-0.3 wt.%Fe alloy, phase morphology and spatial arrangement during solidification was revealed with 1°C temperature resolution. We find that many of the intermetallic phases that have been identified as β-AlFeSi phases in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 25 publications
(44 reference statements)
0
25
1
Order By: Relevance
“…The 3D morphology of β-Fe is a plate-like shape (Fig. 4b1), which is significantly different from the typical needle-like structure in the 2D view, as previously reported in the literature [14]. β-Fe is formed through the peritectic reaction, L + Al3(FeMn)/Al6(FeMn) → α-Al + β-Fe, at 589-597 °C or the eutectic reaction, L → α-Al + Al2Cu + β-Fe, at 546-547 °C [36,37].…”
Section: Characterization Methodscontrasting
confidence: 54%
See 2 more Smart Citations
“…The 3D morphology of β-Fe is a plate-like shape (Fig. 4b1), which is significantly different from the typical needle-like structure in the 2D view, as previously reported in the literature [14]. β-Fe is formed through the peritectic reaction, L + Al3(FeMn)/Al6(FeMn) → α-Al + β-Fe, at 589-597 °C or the eutectic reaction, L → α-Al + Al2Cu + β-Fe, at 546-547 °C [36,37].…”
Section: Characterization Methodscontrasting
confidence: 54%
“…Moreover, the nucleation and growth of Fe phases during the solidification of Al alloys have been investigated using 4D (3D + time) synchrotron X-ray tomography [14][15][16][17]. Eutectic Al2Cu is another important phase in Al-Cu alloys; hence, it is necessary to characterize the 3D morphology of this phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no significant differences in area fraction of b-Al 5 FeSi were found in both unmodified and strontium-modified alloys, as seen in Figure 8(a). Yu et al [17] reported that b-Al 5 FeSi phase nucleates above the Al-Si eutectic reaction temperature while d-Al 3 FeSi 2 phase forms during the Al-Si eutectic reaction in a high purity Al-10Si-0.3Fe alloy. The formation of pre-eutectic b-Al 5 FeSi platelets would consume iron in the liquid and reduce the amount of iron available for the formation of pro-eutectic b-Al 5 FeSi.…”
Section: A Formation Of Intermetallic Phases In Unquenched Alloysmentioning
confidence: 99%
“…[12] The plate-like d-Al 3 FeSi 2 phase may be misidentified as b-Al 5 FeSi phase, particularly in modified Al-Si alloys. [13,14] The iron-rich d phase is termed as d-Al 3 FeSi 2 [12][13][14][15] or d-Al 4 FeSi 2 [16,17] in the literature. In this study, this phase will be described as d-Al 3 FeSi 2 .…”
Section: Introductionmentioning
confidence: 99%